Comparison of antimicrobial activity between ceftolozane–tazobactam and ceftazidime–avibactam against multidrug-resistant isolates of Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. (September 2017) - Alatoom, Adnan; Elsayed, Hashim; Lawlor, Karen; AbdelWareth, Laila; El-Lababidi, Rania; Cardona, Lysettee; Mooty, Mohammad; Bonilla, Maria-Fernanda; Nusair, Ahmad; Mirza, Imran
Highlights: Antimicrobial resistance due to beta-lactamases is the most common mechanism of resistance in Gram-negative bacteria. Studying local susceptibility profiles of multidrug-resistant bacteria is necessary due to regional variations in susceptibility. Ceftazidime–avibactam had good activity against carbapenem-resistant Enterobacteriaceae (CRE) except for those carrying the NDM-1 enzyme. Abstract: Objective: This study compared the activity of ceftolozane–tazobactam and ceftazidime–avibactam against 120 bacterial strains, including extended-spectrum beta-lactamase (ESBL) producers, carbapenem-resistant Enterobacteriaceae (CRE), and Pseudomonas aeruginosa, isolated from patients admitted to Cleveland Clinic Abu Dhabi, United Arab Emirates. Methods: In vitro susceptibility was tested using the Etest strip minimum inhibitory concentration (MIC) method, and PCR was used to characterize the carbapenemase enzymes produced by CRE strains. Results: All 29 ESBL isolates were susceptible to ceftazidime–avibactam (MIC50 0.125 μg/ml), whereas all but one were susceptible to ceftolozane–tazobactam (MIC50 0.38 μg/ml). Twenty-seven (45%) CRE isolates were susceptible to ceftazidime–avibactam (MIC50 ≥256 μg/ml), whereas only six (10%) isolates were susceptible to ceftolozane–tazobactam (MIC50 ≥256 μg/ml). Very few NDM-1 isolates were susceptible to ceftazidime–avibactam, whereas the majority of OXA-48 isolates were susceptible. Twenty-nine (94%) P. aeruginosa isolates were susceptible to ceftazidime–avibactam (MIC50 1.5 μg/ml), whereas 30 (97%) isolates were susceptible to ceftolozane–tazobactam (MIC50 0.75 μg/ml). Conclusions: Ceftolozane–tazobactam and ceftazidime–avibactam showed comparable activity against ESBL and P. aeruginosa, with ceftazidime–avibactam having lower MICs against ESBL isolates and ceftolozane–tazobactam having lower MICs against P. aeruginosa. Ceftazidime–avibactam showed better activity against all CRE isolates except for those carrying the NDM-1 enzyme.